2022
DOI: 10.1097/md.0000000000030251
|View full text |Cite
|
Sign up to set email alerts
|

The hamstrings are more impacted than the quadriceps after severe ankle sprain

Abstract: Ankle sprains (AS) are common in the military population, with a prevalence 5 to 8 times higher than that for civilians. The aim of this study was to evaluate in patients with severe AS the impact of disuse on thigh muscle induced by unloading and immobilization due to care. This study focused on muscle trophicity and dynamometric strength. In this observational prospective study, assessments were repeated at 3 visits: close to injury, 15 and 30 days following the sprain. The injured limb was compared to the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Previous studies assessing quadriceps muscle strength have reported contrasting results. 13 , 23 , 41 The contrasting results may be related to heterogeneity in strength-testing methodology as well as characteristics of the study sample. Thus, further research is needed to clarify this point.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies assessing quadriceps muscle strength have reported contrasting results. 13 , 23 , 41 The contrasting results may be related to heterogeneity in strength-testing methodology as well as characteristics of the study sample. Thus, further research is needed to clarify this point.…”
Section: Discussionmentioning
confidence: 99%
“… 19 , 21 The quadriceps facilitation in turn, as a consequence of the antagonist inhibition phenomenon, leads to hamstring inhibition. In addition, it has been shown that a marked decrease in hamstring muscle strength can be seen early after a severe ankle sprain, 13 as well as in individuals with chronic instability of the ankle. 45 Taken together, these results suggest that a likely immediate reflex inhibition is seen in the muscles directly acting on the ankle and that, at the same time or as a longer-term adaptation, inhibition and facilitation mechanisms arise in muscles acting on more proximal joints.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation